Re/Creating the World through Myths: World-making and Visual Representation of Folk Narratives in the Art of Roberto Feleo - Giron, Manuel Kristoffer C. (Philippine Humanities Review; Vol 19 No 1 (2017), 2018)
Contemporary artist Roberto Feleo is among those from the Philippines who notably represent folk narratives in their art. His artistic practice that has spanned four decades is shaped by his engagement of the myths of the Bagobos, the Bukidnon, and the pinteng legend of the Ifugaos. He has explored unconventional materials and precolonial forms such as the pinalakpak (a medium of sawdust and emulsion traditionally used by carpenters), tau-tao (a term for his three-dimensional representation of humans and characters from folk narratives) and the viriñas (bell jars from the Spanish colonial period used as glass casements for saints and objects of curiosity) in his representations of myths and legends. I investigate what contemporary scholars term as the weaving of connectivities or the worlding that happens in Feleo’s engagement with folk narrative in his art. This tapestry is woven from threads of different worlds: folklore and the contemporary, past and present, traditional and modern, indigenous and colonial, national and global, the everyday and the mythic, and the tensions and intersections that arise from these connectivities. KEYWORDS: worlding, folk narratives, contemporary art, tradition, modernity